A double-layer electrode for the negative side of deep eutectic solvent electrolyte-based vanadium-iron redox flow battery. (15th February 2023) - Ma, Qiang; Fu, Wenxuan; Zhao, Lijuan; Chen, Zhenqian; Su, Huaneng; Xu, Qian
Abstract: This work designs a double-layer porous electrode spliced by carbon paper and graphite felt. A low-porosity carbon paper electrode treated by thermal oxidation is assembled near the membrane, which is used to promote the kinetics of vanadium redox reaction, and the increased hydrophilicity of electrode also facilitates the convective mass transfer process. On the other hand, a high-porosity graphite felt electrode deposited with copper nanoparticles is assembled near the flow field, which has the high permeability, conductivity and interface catalytic efficiency to reduce flow/ions/charge transfer resistances. Cyclic voltammetry illustrates that the copper nanoparticles deposited on the surface of carbon electrode can play the role to enhance the electrochemical activity of the negative electrode with lower potential. Consequently, the double-layer porous electrode is assembled as a negative side of deep eutectic solvent electrolyte-based vanadium-iron redox flow battery (RFB). The experimental study shows this modified RFB has an energy efficiency of 91.8% at the relatively low current density (2 mA cm −2 ), and a peak power density of 12.71 mW cm −2, which are 12.2% and 30.2% higher than that of pristine graphite electrode, respectively. The results demonstrate the superiority of this design strategy of double-layer electrode for potential applications. Highlights: A double-layer electrode is designed for negative side of redox flow battery. The electrode is spliced by carbon paper (CP) and graphite felt (GF). Electrode achieves synergic optimization of transfer and reaction kinetics. Kinetics and hydrophilicity are improved for CP electrode near the membrane. Coupled transfer resistances are reduced for GF electrode near the flow field.